Analysis of a temporal cluster of Shigella boydii isolates in Mpumalanga, South Africa, November to December 2007 - Anthony M. Smith; Karen H. Keddy; Arvinda Sooka; Husna Ismail; Gillian M. DeJong (Journal of Infection in Developing Countries)
Background: Shigellosis is a global human health problem. The disease is most prevalent in developing countries with poor access to safe potable water and sanitation. Shigella boydii is of particular epidemiological importance in developing nations such as African and Asian countries. In the present study, we report on the analysis of a temporal cluster of 29 S. boydii serotype 2 strains, isolated in the Mpumalanga Province of South Africa (SA) over the period of November to December 2007. Methodology: Bacteria were identified as S. boydii using standard microbiological identification techniques and serotyped using commercially available antisera. Susceptibility testing to antimicrobial agents was determined by the Etest. Genotypic relatedness of strains was investigated by pulsed-field gel electrophoresis (PFGE) analysis of digested genomic DNA. Results: The cluster of 29 isolates revealed comparable antimicrobial susceptibility profiles, while dendrogram analysis of PFGE patterns showed that the cluster of isolates grouped together and could clearly be differentiated from a random selection of unrelated S. boydii serotype 2 strains. Our data has strongly suggested that this cluster of isolates may share a common ancestry. However, this cannot be substantiated by epidemiological data because a detailed epidemiological investigation was not conducted. Conclusions: We have documented the first cluster of S. boydii infection in SA. Due to the lack of adequate epidemiological investigation, we cannot emphatically state that an outbreak had occurred. However, we do hypothesis that this was an outbreak for which a waterborne source cannot be excluded. This study has highlighted the urgent need for timely and appropriate systems of epidemiological investigation of all suspected outbreaks of disease in developing countries.